The Effect of Educational Qualifications, Loyalty, and Commitment on Career Development of Tanjung Batu Kundur Hospital Employees Through Work Placement - SUHAIMI, Suhaimi; NAGALIMAN, Nagaliman; SARMINI, Sarmini (PT Keberlanjutan Strategis Indonesia, 2024)
Tanjung Batu Hospital Kundur in Karimun Regency faces job placement and career development issues, where many vital positions do not match the required educational qualifications. This mismatch affects work quality, employee loyalty, and commitment. Therefore, research is needed on how educational qualifications, loyalty, and dedication influence career development through job placement. The population is 160, with the sample used as respondents using the Slovin formula. The number of respondents is 114. Data analysis in this study uses SPSS Application software to test the validity and reliability of the research questionnaire and SEM PLS Application to test the model or research results. The measurement results obtained the following: 1. Commitment positively and significantly affects Job Placement (P-value 0.003), 2. Commitment does not positively affect Career Development (P-value 0.254), 3. Educational Qualification positively and substantially affects Job Placement (P-value 0.000), 4. Educational Qualification positively and substantially affects Career Development (P-value 0.004), 5. Loyalty positively and substantially affects Job Placement (P-value 0.000), 6. Loyalty positively and substantially affects Career Development (P-value 0.025), 7. Job Placement positively and substantially affects Career Development (P-value 0.000), 8. Commitment has a positive and significant indirect effect on Career Development through Job Placement (P-value 0.007), 9. Educational Qualification has a positive and significant indirect effect on Career Development through Job Placement (P-value 0.000), 10. Loyalty positively and significantly indirectly affects Career Development through Job Placement (P-value 0.000).